Espiritualidade e religiosidade em adultos: uma visão sistêmica do desenvolvimento espiritual - Silva, Jessica Sousa (2017)
Considering the importance of religion in the life of human beings and the professional practice of psychologists, we turn to the theme to understand how spiritual and religious values permeate the construction of the subject and its development in adulthood. On this relationship, from the individual to the spiritual values we understand that, whether they are lived individually or from a religious community, they are important aspects in human development. We believe that family value systems as well as spiritual and religious activities become one of the foundations of individuals' choices. The life cycle, therefore, is passed through religious components. In this way, we start from a reading of adult life from the systemic point of view. The research aimed to understand, in the process of development, the construction of spirituality and religiosity by single adults of Christian Seventh-day Adventist families and their relationship to the process of autonomy that characterizes adult life. For this, a qualitative research of narrative approach was designed. Semi-structured interviews were conducted with six adults, three men and three women aged 31-34 years, all of whom declared themselves to be 7th day Adventists. The interviews were transcribed and thematically analyzed which resulted in the following categories: religion, religiosity and spirituality, transmission of spiritual values, sacredness and reflexivity and appropriation. They also indicated that the construction of the meanings attributed to religion, religiosity and spirituality occurred in a process transmitted by the family, religious community and through the coexistence with others that in adulthood was constituted through reflexivity and appropriation